Evaluating the philosophical foundation of 2013 Curriculum - M. Mardiana; Pujiati Suyata (Universitas Negeri Yogyakarta, 2017)
The study was to: (1) identify the interpretation toward the philosophical foundation of 2013 Curriculum; and (2) evaluate the philosophical foundation of 2013 Curriculum. In order to achieve these objectives, the researchers implemented the method of philosophy interpretation, namely a method that might discover an individual's paradigm through the texts or the articles that he or she composed. Furthermore, in order to evaluate the philosophical foundation of 2013 Curriculum the researchers implemented certain criteria and this effort was supported by the expert interview. The data were analyzed by means of hermeneutic method, namely the presence of a relationship among the three elements namely text, interpreter and reader. The conclusions of the study then were as follows: (1) the interpretation toward the philosophical foundation of 2013 Curriculum contained six points namely: (a) establishing and developing the nation's attitude and civilization or the nation's character, (b) developing the curriculum based on the nation's culture, (c) referring to the fact that education had been a process of developing the learning participants' potentials, (d) referring to the fact that education had been based on the nation's culture and experience in the past, (e) referring to the fact that education had been basis of the nation's life continuity and (f) Referring to the fact that education had been adjusted to the life of the learning participants as an individual, a society member and a citizen; (2) the six philosophical reasons namely: (a) perennialism, (b) essentialism, (c) progressivism, (d) pragmatism, (e) existentialism and (f) reconstructionism; (3) the following evaluation results: (a) the philosophical foundation of 2013 Curriculum based on the interpretation results had provided clear educational objectives and functions, (b) the philosophical foundation of 2013 Curriculum had been in accordance to facts, (c) the philosophical foundation of 2013 Curriculum had been in accordance to experiences, (d) the philosophical foundation of 2013 Curriculum had been in accordance to other religions, (e) the Graduates Competence Standards for the Senior High School students in the 2013 Curriculum had been too high and the learning method of 2013 Curriculum for the Elementary School students had been too high and (f) 2013 Curriculum had simple paradigm and it might be attended by the learning participants easily but such paradigm still demanded teachers' creativity within the learning process implementation.